Pengaruh Inovasi Digital terhadap Akuntabilitas Pengelolaan Keuangan Daerah di Kabupaten Purbalingga - Andimulu Hayu Fatimah; Ria Ekanindya Widyaningsih (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
This study aims to analyze the impact of digital innovation on financial management in Purbalingga Regency, focusing on two main systems: the Regional Government Information System (SIPD) and the Village Financial System (SISKEUDES). Digital innovation is considered important to enhance transparency, efficiency, and accountability in public financial management (Lips, 2020; Agostino, Bracci, & Steccolini, 2022). The method used is a qualitative approach with a case study supported by in-depth interviews with application users and previous research (Daffa, 2024; Nadaa & Priyanti, 2023). The findings show that the use of SIPD and SISKEUDES has successfully increased transparency and efficiency in financial reporting in Purbalingga through data integration and public access to information. However, technical issues, limited human resources, and lack of inter-agency cooperation remain obstacles. Efforts by the local government, such as routine training, system updates, and digital literacy improvement, have strengthened digital-based financial governance. Overall, this study shows that the success of digital innovation in public financial management is influenced not only by technology but also by institutional readiness, a culture of transparency, and community involvement in overseeing regional financial management.